75.0k views
0 votes
Which of the following is equivalent to −3(2p − 4q)?

−5p − 7q
−5p + 12q
−6p − 4q
−6p + 12q

2 Answers

3 votes

Answer:


\sf \: d) \: -6p + 12q

Explanation:

Now we have to,

→ simplify the given expression.

The expression is,

→ -3(2p - 4q)

Let's simplify the expression,

→ -3(2p - 4q)

→ -3(2p) - 3(-4q)

→ (-3 × 2)p - (3 × -4)q

→ -6p - (-12)q

→ -6p + 12q

Hence, answer is -6p + 12q.

User Synergetic
by
5.3k points
4 votes

Answer:

-6p+12q

Explanation:

−3(2p − 4q)

Distribute the -3

-3 * 2p -3 * -4q

-6p+12q

User Swapnil Pandit
by
5.0k points